ANALISIS ANALISIS PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DALAM PELAYANAN PADA PT MANDALA TOURS & TRAVEL DI MAKASSAR - Asse, Maslinda; Machmud, Mukarramah; Renold (Politeknik Pariwisata Bali, 2025)
This study aims to analyze the influence of work environment and workload on employee performance in service delivery at PT Mandala Tours & Travel in Makassar. Specifically, the objectives of this study are: (1) to analyze the influence of the work environment on employee performance in service delivery; (2) to analyze the influence of workload on employee performance in service delivery; and (3) to analyze the simultaneous influence of work environment and workload on employee performance in service delivery.. The research employed a quantitative approach, involving two independent variables: work environment (X?) and workload (X?), and one dependent variable: employee performance (Y). The data were collected using a questionnaire instrument based on a Likert scale. The population of this study comprised all employees of PT Mandala Tours & Travel, totaling 12 individuals, all of whom were also used as the research sample through a saturated sampling technique. Data collection was carried out using questionnaires, and the data were analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that the work environment has a partially positive and statistically significant effect on employee performance. In contrast, workload does not have a significant partial effect on employee performance. However, when tested simultaneously, the work environment and workload collectively exert a significant influence on employee performance. Based on these findings, it is recommended that the company continuously improve the quality of the work environment and manage workloads effectively to enhance the overall quality of service performance.